Síntese e caracterização de tungstatos de cério e estrôncio para fins catalíticos - Moriyama, André Luiz Lopes (2011)
The main goal of this work was to produce nanosized ceramic materials of the family of the tungstates (tungstates of cerium and strontium), and test them for their catalytic activity in processes involving the transformation of methane (CH4). The methodology used for the synthesis of the ceramic powders involved the complexation combining EDTA-citrate. The materials characterization was performed using simple and differential thermogravimetry, x-ray diffraction, transmission electron microscopy, and energy dispersive spectroscopy (EDS). The microstructure analysis was performed using the refinement by the Rietveld method, and the crystallite size and distribution of the materials was elucidate by the Scherrer and Williamson-Hall methods. The conditions of the synthesis process for the three envisaged materials (SrWO4, SrWO4 using tungsten oxide concentrate as raw material, and Ce2(WO4)3) were adjusted to obtain a single phase crystalline material. The catalytic tests were carried out in the presence of methane and synthetic air, which is composed of 21% O2 and 79% N2. The analysis of the conversion of the reaction was done with the aid of an fourier transform infrared device (FTIR). The analysis showed that, structurally, the SrWO4 produced using raw materials of high and poor purity (99% and 92%, respectively) are similar. The ideal parameters of calcination, in the tested range, are temperature of 1000 °C and time of calcination 5 hours. For the Ce2(WO4)3, the ideal calcination time and are temperature 15 hours and 1000°C, respectively. The Williamson-Hall method provided two different distributions for the crystallite size of each material, whose values ranged between the nanometer and micrometer scales. According to method of Scherrer, all materials produced were composed of nanometric crystallites. The analyses of transmission electron microscopy confirmed the results obtained from the Williamson- Hall method for the crystallite size. The EDS showed an atomic composition for the metals in the SrWO4 that was different of the theoretical composition. With respect to the catalytic tests, all materials were found to be catalytically active, but the reaction process should be further studied and optimized.